2020
DOI: 10.1016/j.vph.2019.106633
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota are critical for vascular physiology: Germ-free status weakens contractility and induces sex-specific vascular remodeling in mice

Abstract: Commensal microbiota within a holobiont contribute to the overall health of the host via mutualistic symbiosis. Disturbances in such symbiosis is prominently correlated with a variety of diseases affecting the modern society of humans including cardiovascular diseases, which are the number one contributors to human mortality. Given that a hallmark of all cardiovascular diseases is changes in vascular function, we hypothesized that depleting microbiota from a holobiont would induce vascular dysfunction. To test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…Overall, these results constitute a fundamental discovery of the essential nature of microbiota in blood pressure regulation (107). Corroborating evidence that microbiota is critical for vascular tone and blood pressure control, male and female GF mice also present a decrease in the contraction of resistance arteries (26). However, these changes are more pronounced in GF males than in GF female mice.…”
Section: Impact Of the Gut Microbiota On The Cardiovascular Systemmentioning
confidence: 58%
See 1 more Smart Citation
“…Overall, these results constitute a fundamental discovery of the essential nature of microbiota in blood pressure regulation (107). Corroborating evidence that microbiota is critical for vascular tone and blood pressure control, male and female GF mice also present a decrease in the contraction of resistance arteries (26). However, these changes are more pronounced in GF males than in GF female mice.…”
Section: Impact Of the Gut Microbiota On The Cardiovascular Systemmentioning
confidence: 58%
“…CVD is a multifactorial disorder influenced by environmental and genetic factors. Adding to the complexity of CVD, growing evidence supports that the gut microbiota and its metabolites contribute to cardiovascular dysfunction (22)(23)(24)(25)(26)(27)(28)(29). In addition, the gut microbiota also contributes to ethanol-induced cellular injury (30)(31)(32)(33)(34).…”
Section: Stating the Problem Ethanol And The Cardiovascular Systemmentioning
confidence: 99%
“…However, this may slightly limit the translatability of these data to future human recipients as some studies have demonstrated variations to GF physiology including alterations in vascular phenotypes and the development of metabolic dysfunction. [40][41][42] Second, our decision to use a single lean and obese donor in each cohort rather than gut microbiota from a mixed group may also reduce the generalizability of the data. Lastly, important questions exist regarding the amount of time that is required for transplantations to elicit physiological changes, as well the duration before those changes begin to wane.…”
Section: Discussionmentioning
confidence: 99%
“…Germ free mice have been extensively used for deciphering some mechanisms linked to diseases, such as Type 2 diabetes mellitus, T2DM [15] behavioral functions at the gut-brain axis and autism [16], cardiovascular diseases [17] and cancer [18]. The use of therapeutics to treat these diseases is also investigated with the use of germ-free colonies and use of a standardized protocol and method would be of interest for future studies.…”
Section: Expected Results and Discussionmentioning
confidence: 99%